2020
DOI: 10.1002/bjs5.50346
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of faecal immunochemical testing in patients with symptomatic colorectal cancer

Abstract: Background: The aim of this study was to determine the diagnostic accuracy of the faecal immunochemical test (FIT) for detecting colorectal cancer in symptomatic patients. Methods: This was a prospective study of patients with bowel symptoms. Stool samples were collected during rectal examination. The HM-JACKarc assay (Kyowa Medex, Tokyo, Japan) was used to quantify faecal haemoglobin (Hb); positive results were those with at least 10 g Hb/g faeces. Two-by-two tables and receiver operating characteristic (ROC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 30 publications
1
29
0
Order By: Relevance
“…These results, which focus solely on patients with RB may be added to an increasing body of evidence that the FIT could be extended for use in symptomatic patients with higher risk symptoms, including patient cohorts with rectal bleeding. [14,19–24] Amongst this evidence, two studies looked specifically at the FIT in RB; Högberg et al reported a sensitivity of 96.2% and NPV of 99.7% for CRC [19], and Digby et al reported that patients with f ‐Hb <10 µg/g were very unlikely to have serious bowel disease (1.2%) or CRC (0.03%). [14]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results, which focus solely on patients with RB may be added to an increasing body of evidence that the FIT could be extended for use in symptomatic patients with higher risk symptoms, including patient cohorts with rectal bleeding. [14,19–24] Amongst this evidence, two studies looked specifically at the FIT in RB; Högberg et al reported a sensitivity of 96.2% and NPV of 99.7% for CRC [19], and Digby et al reported that patients with f ‐Hb <10 µg/g were very unlikely to have serious bowel disease (1.2%) or CRC (0.03%). [14]…”
Section: Discussionmentioning
confidence: 99%
“…These results, which focus solely on patients with RB may be added to an increasing body of evidence that the FIT could be extended for use in symptomatic patients with higher risk symptoms, including patient cohorts with rectal bleeding. [14,[19][20][21][22][23][24]…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…NICE guidelines recommend it for the patient with unexplained changes in bowel habits and iron deficiency anemia (patients aged 60 and over, even in the absence of iron deficiency) for use in primary care or screening for suspected CRC [ 88 ]. FIT may help effectively excluded CRC among symptomatic patients [ 100 ] and, in conjunction with clinical assessment, may safely and objectively determine individual risk of CRC for further decisions about urgent or routine management [ 101 ]. Moreover, FIT is preferable to the gFOBT in terms of the detection rate, positive predictive value and participation rate [ 102 ].…”
Section: Diagnosticmentioning
confidence: 99%
“…This strategy involves giving advice to patients that their symptoms are unlikely to be due to significant GI disease, but they should seek advice should their symptoms return, continue, or worsen. Further, it is now clear that FIT can be employed in this context for all symptomatic patients, not only lowrisk 9,10 as recommended in NICE NG12 6 and DG30, 7 but also those who report high-risk symptoms, [11][12][13][14][15] particularly rectal bleeding. 16 However, uncertainty remains around a numerical f-Hb threshold to discriminate between those who are and are not likely to benefit from investigation.…”
Section: Introductionmentioning
confidence: 99%